A HARMONISE'd approach to building security-driven urban resilience: a call to arms. Issue 1 (4th April 2016) - Coaffee, Jon; Clarke, Jonathan; Davis, Peadar T.
Abstract : Purpose: – Resilience is a topical concept in many academic disciplines world-wide and also among practitioners. In Europe, however, the current conceptualisations of urban resilience are highly specific to institutional contexts, national cultures and traditions and emergent risks faced in particular countries and their urban areas. The differences in how urban resilience is understood and applied are important, and yet such differences are only scarcely addressed in current resilience literature. This paper draws from the EU's Seventh Framework Programme for research, technological development and demonstration security project HARMONISE – A Holistic Approach to Resilience and Systematic Actions to Make Large Scale Built Infrastructure Secure. Design/methodology/approach: – The project develops a comprehensive, multifaceted, yet mutually reinforcing concept for the enhanced security, resilience and sustainability of urban infrastructure and development. As part of the project, 61 experts were interviewed in six European countries (UK, Ireland, Germany, Italy, Spain and Finland) to establish a comprehensive understanding of the current role and position of resilience in urban-built infrastructure. These interviews elicit the current views of professionals from a number of contributory and competing disciplines. Findings: – Results indicate that there is no shared holistic understanding of urban resilience in Europe. The definitions of the concept vary across disciplines. The research identifies that there are a number of existing theoretical and practice gaps that require to be addressed. Originality/value: – This paper presents a number of research and practice "gaps" which are being addressed in the HARMONISE project and which require to be addressed by the wider academic and practice communities.